Determining IPO prices for innovative firms: the case of young French bio-medtech firms - POINCELOT, EVELYNE; POINCELOT, DOMINIQUE (Bankers, Markets & Investors, 2019)
The large number of French biotech firms that have recently gone public prompts us to analyse the role and characteristics of their initial backers and their influence in determining the offer price at the time of the IPO. We assume the offer price is set so as to underprice companies in conjunction with the exit motives of their main shareholders and the nature and characteristics of the venture capital firms backing them. The paper characterizes listed bio-medtech firms, although the results sometimes fail to reveal underpricing for the 39 bio medtech firms that went publicon Euronext Paris between 2010 and 2016.